Probing Polymer Contact Electrification by Gamma-Ray Radiation - Zhang, Dong Li; Shi, Jian Min; Wang, Zhong Lin; Tang, Wei (Frontiers in Materials, 2022)
Triboelectric Nanogenerators (TENGs) have been regarded as an effective method to solve the energy problem since demonstrated in 2012. Due to its high-power generation and low-cost, TENGs have been widely applied in fields of energy, security, biomedical, environment, and so on. For now, many researchers are focusing on the contact electrification (CE) and surface modification, in order to find out the fundamental CE mechanism and approaches to further enhance the performance of TENG devices. In this work, we employ gamma radiation (γ ray) to induce surface modifications on the dielectric materials (polymers in this work) and study its influence on CE. It is found that, due to the high energy of γ ray, some chemical bonds in polymers are destroyed, and reformed. This changes the electron density of the polymer molecule, and thus varies the electron transfer ability of the dielectric materials. Afterwards, polytetrafluoroethylene (PTFE) and polyvinyl chloride (PVC) become more negative, and polyethylene terephthalate (PET) becomes the opposite. Kapton, in particularly, keeps stable even after 1 MGy-dose radiation. This study reconfirms that electron transfer is the dominant process for polymers-related CE. And it also suggests that triboelectric nanogenerators could be fabricated with materials possessing a high anti-radiation ability, and used for sensing or energy generation in space, or environments where radiation exists.